"End-of-Life Care? I'm not Going to Worry About That Yet." Health Literacy Gaps and End-of-Life Planning Among Elderly Dialysis Patients. (10th March 2017) - Ladin, Keren; Buttafarro, Katie; Hahn, Emily; Koch-Weser, Susan; Weiner, Daniel E
Abstract: Purpose: Between 2000 and 2012, the incident dialysis population in the United States increased by nearly 60%, most sharply among adults 75 years and older. End-of-life (EOL) conversations among dialysis patients are associated with better patient-centered outcomes and lower use of aggressive interventions in the last month of life. This study examined how health literacy may affect engagement, comprehension, and satisfaction with EOL conversations among elderly dialysis patients. Design and Methods: Qualitative/descriptive study with semi-structured interviews about health literacy, EOL conversations, and goals of care with 31 elderly dialysis patients at 2 centers in Boston. Themes were interpreted in the context of Nutbeam's health literacy framework. Results: Despite high mortality risk in this population, only 13% of patients had discussed EOL preferences with physicians, half had discussed EOL with their social network, and 25% of participants explicitly stated that they had never considered EOL preferences. Less than 30% of participants could correctly define terminology commonly used in EOL conversations. Analyses yielded 5 themes: (1) Misunderstanding EOL terminology; (2) Nephrologists reluctant to discuss EOL; (3) Patients conforming to socially constructed roles; (4) Discordant expectations and dialysis experiences; and (5) Reconciling EOL values and future care. Patients had limited understanding of EOL terminology, lacked of opportunities for meaningful EOL discussion with providers and family, resulting in uncertainty about future care. Implications: Limited health literacy presents a substantial barrier to communication and could lead to older adults committing to an intensive pattern of care without adequate information. Clinicians should consider health literacy when discussing dialysis initiation.